Effectiveness of The Implementation of The Course of Curriculum KKNI in Improving The Learning Quality of The Country Law Course in The Country Law Study Programme - Ramadani, Ramadani; Susandi, Aidil; Hamonangan, Mhd Dedi (Sekolah Tinggi Agama Islam Sumatera Medan, 2024)
The course of constitutional law is a compulsory course in the faculty of sharia and law, this course is a basic course to master the study of constitutional law explicitly (textual and development of the times). With regard to that, this study aims to analyse the aspects of curriculum preparation norms according to statutory regulations, the effectiveness of curriculum implementation in improving the quality of learning in constitutional law courses at the Faculty of Sharia and Law State Islamic University of North Sumatra Medan. The research model used is the CIPP (Context, Input, Process and Product) evaluation model. This model is used to determine the implementation of learning process standards in the Constitutional Law (Siyasah) Study Programme, Faculty of Sharia and Law, State Islamic University of North Sumatra. The results showed that in theory the level of norms the existence of regulations regarding the curriculum is in accordance with statutory regulations ranging from laws, government regulations, presidential regulations, ministerial regulations to the rector's regulations of the State Islamic University of North Sumatra Medan is in accordance with the theory of the level of norms. Then, in the results of research on the implementation of the effectiveness of the constitutional law curriculum in the constitutional law study programme (siyasah), there are still many constitutional law students who do not understand the study of constitutional law explicitly.